Labor market drilldowns for the Milwaukee Area Workforce investment Board (MAWIB) - ALL - (:unkn) unknown (My University, 2012)
Assisting workers with prison records is one of the greatest employment challenges facing the Milwaukee Area Workforce Investment Board for 2013. This drilldown prepared by the Employment and Training Institute examined Wisconsin Department of Corrections records on adults incarcerated in state correctional facilities. The DOC records show incarceration rates at epidemic levels for African American males from Milwaukee County. At least 27,060 black males ages 20 through 64 with a Milwaukee County address (as the last found home address) have been incarcerated in the state DOC system. These included 5,571 men currently incarcerated (as of 2012) and another 21,489 previously incarcerated. The totals do not include those incarcerated in federal prisons, state juvenile correctional facilities, or county and city jails. The estimated incarceration rate has reached 58% for African American men in their early 30s from the county.
Keywords: job vacancies; job skills mismatch; job spatial mismatch